Strength Comparison of Unreinforced Masonry Wall Made of Different Types of Brick - Mohammad Rafiqul Islam; Abul Hasnat; Raquib Ahsan; Ahmed Tohameem Alam (Journal of Rehabilitation in Civil Engineering)
An attempt has been made in this study to correlate compressive strength, shear strength, and wall stiffness for clay burnt bricks with frog mark and machine-made bricks without frog mark. In this experimental study, 8 prisms and 8 unreinforced masonry (URM) walls (254 mm) with a size of 1524 mm X 914 mm were constructed with two different types of bricks, i.e., clay burnt brick with frog mark and machine-made brick without frog mark. Two types of mortar thicknesses 13 mm and 19 mm were used in the test specimens. The prism specimens were tested under axial compression load normal to the bed joints and the wall specimens were tested under horizontal incremental cyclic loading along with the constant axial compressive load. Lateral loading was applied using a loading control pattern. The specimens were tested under cyclic loading conditions displacing them laterally, along the axis of the walls and their load-deformation behavior was measured by dial gauges. It is observed that with increasing mortar thickness prism, ultimate strength increases 18.0% for clay burnt brick and with increasing mortar thickness prism, ultimate strength increases 1.3% for machine-made brick. On the other hand, with increasing the mortar thickness, ultimate shear strength decreases 9.6% for clay burnt brick with frog mark and with increasing mortar thickness ultimate, shear strength decreases 8.0% for machine-made bricks without frog mark. In clay burnt brick shear strength is 12.5% more than machine-made brick. With increasing the mortar thickness, ductility decreases 22.0% for clay burnt brick and 20.0% for machine-made bricks. Based on the findings, it is stated that clay burnt brick is preferable to machine manufactured brick. This study will aid in the comprehension of the behavior of both types of bricks used in masonry construction, given that masonry is a common building material.